Answer:
9.
h(x)=-x-1
let y =-x-1
interchanging role of x & y
x=-y-1
y=-x-1
h-¹(x)=-x-1
again
f(x)=(2-3x)/2
let
y=(2-3x)/2
interchanging role of x & y
x=(2-3y)/2
2x-2=-3y
y=(2-2x)/3
f-¹(x)=(2-2x)/3
<u>G</u><u>i</u><u>v</u><u>e</u><u>n</u><u> </u><u>f</u><u>u</u><u>n</u><u>c</u><u>t</u><u>i</u><u>o</u><u>n</u><u> </u><u>a</u><u>r</u><u>e</u><u> </u><u>n</u><u>o</u><u>t</u><u> </u><u>i</u><u>n</u><u>v</u><u>e</u><u>r</u><u>s</u><u>e</u><u> </u><u>o</u><u>f</u><u> </u><u>e</u><u>a</u><u>c</u><u>h</u><u> </u><u>o</u><u>t</u><u>h</u><u>e</u><u>r</u><u>.</u>
10.
f(x)=-x+3
let y=-x+3
interchanging role of x & y
x=-y+3
y=3-x
f-¹(x)=-x+3
equal to g(x)=-x+3
<u>Given function are</u><u> inverse of each other.</u>
Answer:
y*y*y*y*y*y
Step-by-step explanation:
![(y^{2})^{3} = y^{6} = y*y*y*y*y*y](https://tex.z-dn.net/?f=%28y%5E%7B2%7D%29%5E%7B3%7D%20%3D%20y%5E%7B6%7D%20%3D%20y%2Ay%2Ay%2Ay%2Ay%2Ay)
--8+4+6=2
Hope it helps :-)
Yes, that is correct because if you want to reduce it you divide 8 by 2 and 10 by 2 and you get 4/5